Design of an optical meter - Kho, Yin Mei (2017)
Low-Emissivity coatings of the building help in reflecting heat energy. It reflects heat from the outer side, hence reducing solar gain and cooling costs during the warm months. In countries where cooling months are present, the coatings help in retaining heat energy within the interior of the house. This plays a huge part in reducing the energy loss hence, lowering the heating costs. In this report, a detailed procedure of designing an optical meter that measures transmittance and/or reflectance of the glass or window film is discussed.